In-Vivo Induced CAR-T Cell for the Potential Breakthrough to Overcome the Barriers of Current CAR-T Cell Therapy - Xin, Tianqing; Cheng, Li; Zhou, Chuchao; Zhao, Yimeng; Hu, Zhenhua; Wu, Xiaoyan (Frontiers in Oncology, 2022)
Chimeric antigen receptor T cell （CAR-T cell）therapy has shown impressive success in the treatment of hematological malignancies. However, systemic toxicity and the complex manufacturing process of current autologous CAR-T cell therapy hinder its broader application. Universal CAR-T cells were developed to simplify the production process through isolation and editor of allogeneic T cells from healthy persons. But the allogeneic CAR-T cells recently encountered safety concerns and were halted in the clinical trial by FDA. Thus, there is an urgent need to seek new ways to overcome the barriers of current CAR-T cell therapy. In-Vivo induced CAR-T cells by nanocarriers loading with CAR-genes and gene-editing tools have shown an exciting efficiency to regress leukemia and a surprising reduction of systemic toxicity in a mouse model. The in-situ programming of autologous T-cells avoids the safety concern caused by allogeneic T cells and the manufacture of nanocarriers are easy to realize process standardization. Therefore, the in-vivo induced CAR-T cells is a potential breakthrough to overcome the above-mentioned limitations of current CAR-T cell therapy. Here we provided a review on CAR structures, gene-editing tools, and gene delivery techniques applied in immunotherapy for helping the design and development of new in-vivo induced CAR-T cells.